2017
DOI: 10.3390/w9030178
|View full text |Cite
|
Sign up to set email alerts
|

Drought Characteristic Analysis Based on an Improved PDSI in the Wei River Basin of China

Abstract: Abstract:In this study, to improve the efficiency of the original Palmer Drought Severity Index (PDSI_original), we coupled the Soil and Water Assessment tool (SWAT) and PDSI_original to construct a drought index called PDSI_SWAT. The constructed PDSI_SWAT is applied in the Wei River Basin (WRB) of China during 1960-2012. The comparison of the PDSI_SWAT with four other commonly used drought indices reveals the effectiveness of the PDSI_SWAT in describing the drought propagation processes in WRB. The whole WRB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 42 publications
1
8
0
1
Order By: Relevance
“…It was found that the study area showed a general trend of drying out by Mann-Kendall test. Zou et al (2017) founded that a trendency to dry out can be observed during 1961 to 2012 in the WRB, this is consistent with the findings of this paper. The results also found that both the accumulation time of extreme drought and the maximum time of extreme drought in Guanzhong Plain were much higher than those in other regions, which indicated that the drought situation in Guanzhong area was more severe.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that the study area showed a general trend of drying out by Mann-Kendall test. Zou et al (2017) founded that a trendency to dry out can be observed during 1961 to 2012 in the WRB, this is consistent with the findings of this paper. The results also found that both the accumulation time of extreme drought and the maximum time of extreme drought in Guanzhong Plain were much higher than those in other regions, which indicated that the drought situation in Guanzhong area was more severe.…”
Section: Discussionsupporting
confidence: 93%
“…This can subsequently be used in regional risk assessment. In climate studies, PCA is mostly applied to reduce the number of variables and produce factors that will explain most of the variance or analyze spatial and temporal variability of various phenomena such as drought (see [16,39,40,48,65,66,86].…”
Section: Spatial Patterns Identificationmentioning
confidence: 99%
“…It can clearly reveal the various change periods hidden in the time series and reflect the change trend of the system in different time scales to estimate the future trend of the data series [28]. Because the change of climate characteristics caused by precipitation has multi-time scale and is continuous, the continuous wavelet transforms using complex Morlet wavelets is a robust tool to analyze the change characteristics of years of PDSI time series [29]. However, there are few studies on the correlation analysis between the variation period of PDSI and the area of surface waters.…”
Section: Introductionmentioning
confidence: 99%